2022
DOI: 10.1002/jccs.202200195
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of promising cholinesterase inhibitors for Alzheimer's disease treatment through DFT, docking, and molecular dynamics studies of eugenol derivatives

Abstract: Cholinesterase enzymes are promising drug targets for the symptomatic treatment of Alzheimer's disease. Indeed, the activity inhibition of these acetylcholine-degrading enzymes leads to improved neurocognitive function. The present work, attempted to identify eugenol derivatives possibly capable of inhibiting the acetylcholine enzymes, by implementing density functional theory (DFT), docking and molecular dynamics methods. The investigated compounds exhibited moderate to high affinity toward the target protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The stability of a protein undergoing MD simulation is assessed by one of the important parameter known as the radius of gyration (Rg) which is defined as the mass‐weighted RMS distance of atoms from their common center of mass [40,48,49] . The analysis of structural compactness was done by analyzing the radius of gyration (Rg) in order to comprehend the structural stability of AChE alone and in complexation with Donepezil, D10 and D13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of a protein undergoing MD simulation is assessed by one of the important parameter known as the radius of gyration (Rg) which is defined as the mass‐weighted RMS distance of atoms from their common center of mass [40,48,49] . The analysis of structural compactness was done by analyzing the radius of gyration (Rg) in order to comprehend the structural stability of AChE alone and in complexation with Donepezil, D10 and D13.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of a protein undergoing MD simulation is assessed by one of the important parameter known as the radius of gyration (Rg) which is defined as the mass-weighted RMS distance of atoms from their common center of mass. [40,48,49] The analysis of structural compactness was done by analyzing the radius of gyration structural integrity of AChE and its docked complexes with Donepezil, D10 and D13 was intact, with an average Rg values for AChE, AChE-Donepezil, AChED10 and AChED13 of 2.31, 2.26 2.29 and 2.30 nm, respectively. The stable structural dynamics can be observed from these Rg values depicting the stable dynamics over the course of 100 ns of MD simulation.…”
Section: Gyration Sasa and Energy Analysismentioning
confidence: 99%
“…Furthermore, L16's backbone is well covered by these interactions. Additionally, prior investigations have shown that the residues with which L16 interacted are some of the important sites controlling the inhibition of BuChE [ 48 , 49 ].
Figure 7 (a) 3D and (b) 2D diagram revealing the interactions involved between L16 and BuChE receptor.
…”
Section: Resultsmentioning
confidence: 99%
“…Radius of gyration (Rg) is an important parameter to evaluate the stability of proteins in MD simulations [ 48 ]. Figure 10 (a) illustrates the Rg graphs related to the studied systems.…”
Section: Resultsmentioning
confidence: 99%
“…Alzheimer's disease (AD), the most common type of neurodegenerative disorder with a high incidence (60%-80%) and mortality rate, is estimated that the number of Alzheimer's patients in the word will reach 100 million by the middle of this century. [1,2] Until now, cholinesterase inhibitors have been the mainstay of DOI: 10.1002/mnfr.202200816 symptomatic treatment, possibly helping to improve cholinergic neurotransmission by inhibiting the excessive hydrolysis of acetylcholine (Ach) by acetylcholinesterase. [3] Donepezil, galantamine, and rivastigmine of treatments with long-term oral medications have been shown to be effective but the side effects cannot be ignored, including nausea, diarrhea, insomnia, and a slower heart rate.…”
Section: Introductionmentioning
confidence: 99%